The essential kinase ATR: ensuring faithful duplication of a challenging genome - Saldivar, Joshua C.; Cortez, David; Cimprich, Karlene A. (Nature reviews. Molecular cell biology, 2017)
Key Points Ataxia telangiectasia and Rad3-related (ATR) is an essential kinase that is active in S phase, senses stressed replication forks and orchestrates a multifaceted response to DNA replication stress. This response helps ensure completion of DNA replication and maintains the integrity of the genome. ATR and its binding partner, ATR-interacting protein (ATRIP), are recruited to stalled forks through direct interactions with the replication protein A–single-stranded DNA (RPA–ssDNA) complex that forms at stressed replication forks. When bound to ssDNA, the kinase activity of ATR is stimulated by the ATR-activating domains of topoisomerase II binding protein 1 (TOPBP1) or Ewing tumour-associated antigen 1 (ETAA1), which are independently recruited to junctions between ssDNA and double-stranded DNA (dsDNA) and to RPA–ssDNA, respectively. ATR activity can be amplified by generating more ssDNA–dsDNA junctions at individual replication forks, through feed-forward signalling loops and by post-translational modifications of the signalling complexes. When activated, ATR directs the replication stress response to arrest the cell cycle, block origin of replication firing and stabilize and repair stalled replication forks. ATR and its effector, checkpoint kinase 1 (CHK1), are active both during an unperturbed S phase, to prevent excessive origin firing, and in response to replication stress, to slow DNA replication. However, this negative regulation of replication initiation does not prevent the firing of dormant origins within a replication domain, which can rescue replication completion without requiring the damaged fork to restart. ATR phosphorylates numerous replisome proteins and repair factors that prevent fork collapse and the formation of DNA breaks. These post-translational modifications regulate the remodelling of replication forks and subsequent nuclease-dependent cleavage and/or resection of forks. They also regulate pathways needed to repair stalled forks and restart DNA synthesis. Replication stress is controlled by the kinase ataxia telangiectasia and Rad3-related (ATR), which senses and resolves threats to DNA integrity. ATR activation is complex and involves a core set of components that recruit ATR to stressed replication forks, stimulate its kinase activity and amplify downstream signalling to maintain the stability of replication forks. One way to preserve a rare book is to lock it away from all potential sources of damage. Of course, an inaccessible book is also of little use, and the paper and ink will continue to degrade with age in any case. Like a book, the information stored in our DNA needs to be read, but it is also subject to continuous assault and therefore needs to be protected. In this Review, we examine how the replication stress response that is controlled by the kinase ataxia telangiectasia and Rad3-related (ATR) senses and resolves threats to DNA integrity so that the DNA remains available to read in all of our cells. We discuss the multiple data that have revealed an elegant yet increasingly complex mechanism of ATR activation. This involves a core set of components that recruit ATR to stressed replication forks, stimulate kinase activity and amplify ATR signalling. We focus on the activities of ATR in the control of cell cycle checkpoints, origin firing and replication fork stability, and on how proper regulation of these processes is crucial to ensure faithful duplication of a challenging genome.